Generative Allegories of Oppression and Emancipation: Reflecting with Computational Social Models - Ricardo Sosa (Diseña, 2022)
This paper presents a computational approach to growing artificial societies (agent-based simulations) as an explicit, accessible, and systematic tool to visualize and generate insights and new questions about Paulo Freire’s concepts of oppression and emancipation. These models do not make claims of validity or prediction, instead, their value is to structure our thinking and support our understanding. Here, I use computational social simulations as generative allegories to reflect upon the role of designers in participatory, co-design, and social design contexts. The paper shows how Freirean ideas can help reframe design as a pedagogical craft based on dialogue and collective inquiry.